2021
DOI: 10.1177/10600280211050120
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Creatinine-Based Kidney Function With and Without Sex Assigned at Birth Among Transgender Adults

Abstract: Background Clinicians use sex-based kidney function estimating equations, but the appropriate sex modifier for transgender adults undergoing hormone therapy (HT) is undetermined. Objectives Compare median estimated creatinine clearance (eCrCL; Cockcroft-Gault) and estimated glomerular filtration rates (eGFRs; Modification of Diet in Renal Disease [MDRD] and Chronic Kidney Disease Epidemiology Study [CKD-EPI]) before and during HT when estimated with and without sex assigned at birth. Methods Single-system retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In this case, we observed that the patient's serum testosterone level continued to increase for 3 years preceding the referral, and sCre was eventually elevated at the time of referral. Testosterone, the primary androgen in males, can stimulate muscle protein synthesis via testosterone receptors in skeletal muscle 2–5 . Although a trend in sCre during this period was not confirmed, the patient's sCre and weight increased with normal kidney function, suggesting that the serum testosterone levels increased muscle mass, thereby increasing sCre of the patient regardless of kidney function.…”
Section: Time From Referral −10 Years −3 Years 0 (At Referral) +1 Yearmentioning
confidence: 80%
“…In this case, we observed that the patient's serum testosterone level continued to increase for 3 years preceding the referral, and sCre was eventually elevated at the time of referral. Testosterone, the primary androgen in males, can stimulate muscle protein synthesis via testosterone receptors in skeletal muscle 2–5 . Although a trend in sCre during this period was not confirmed, the patient's sCre and weight increased with normal kidney function, suggesting that the serum testosterone levels increased muscle mass, thereby increasing sCre of the patient regardless of kidney function.…”
Section: Time From Referral −10 Years −3 Years 0 (At Referral) +1 Yearmentioning
confidence: 80%
“…5 In contrast, eCrCl and eGFR did not significantly change in transgender women (estrogen group) when using the sex assigned at birth but significantly worsened when using the identified gender. 5 Interestingly, serum creatinine significantly increased over time among transgender men but did not significantly change in transgender women. 5 These results highlight the significant effect of the sex coefficient on the assessment of renal function among various estimating equations, despite relatively small absolute changes in serum creatinine.…”
mentioning
confidence: 80%
“…5 Interestingly, serum creatinine significantly increased over time among transgender men but did not significantly change in transgender women. 5 These results highlight the significant effect of the sex coefficient on the assessment of renal function among various estimating equations, despite relatively small absolute changes in serum creatinine. Although serum creatinine may be more similar between estimating equations using identified gender compared to sex assigned at birth after 6 months of gender-affirming hormone therapy, clinicians should be aware that transgender men may have an overestimation of renal function and transgender women may have an underestimation of renal function when using creatinine-based equations.…”
mentioning
confidence: 91%
See 2 more Smart Citations